PORTFOLIO ASSESSMENT IMPLEMENTATION MODEL IN ISLAMIC RELIGIOUS LEARNING: A CASE STUDY AT STATE ISLAMIC SENIOR HIGH SCHOOL 1 BOJONEGORO - Rokhman, Roli Abdul; Hidayah, Syarifatul Fitri; Khunaivi, Herman (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2024)
As it was a common fact in the field, incomplete assessment processes and results were the cause of a weak educational assessment system, which had an impact on weakening students’ motivation and learning creativity. Portfolio assessment was an alternative to an authentic and comprehensive assessment system that could increase students' learning spirit and creativity. This study aimed to determine how portfolio assessment was implemented in Islamic religious learning at Madrasah Aliyah 1 Bojonegoro. The method used​ in this study was qualitative with a case study design. The subject of this study was the Head of the curriculum, Head of students, Islamic religious teachers, guardians of students, academic supervisors, and selected alumni. The case study data analysis was carried out through stages: collecting data, analyzing data, interpreting data, and making conclusions. The results showed that the implementation of portfolio assessment was carried out in two stages: first, assessment of the indicator stage, and second, assessment of the artifactartefactThe portfolio assessment process was carried out through four stages, namely, 1) stage of collecting evidence of work, 2) stage of selecting evidence of work, 3) work reflection stage, and 4) work exhibition stage. It was expected that the results of this study could develop an effective and efficient model for implementing portfolio assessment to increase students' learning motivation and creativity in joining the process of Islamic religious learning.